JNK Pathway-Associated Phosphatase/DUSP22 Suppresses CD4+ T-Cell Activation and Th1/Th17-Cell Differentiation and Negatively Correlates with Clinical Activity in Inflammatory Bowel Disease - Zhou, Rui; Chang, Ying; Liu, Jing; Chen, Min; Wang, Hongling; Huang, Meifang; Liu, Shi; Wang, Xiaobing; Zhao, Qiu (Frontiers in Immunology, 2017)
This study aimed to investigate the role of JKAP in inflammatory bowel disease (IBD). JKAP expression was analyzed in the intestinal mucosa of 81 IBD patients and 25 healthy controls (HCs) by qPCR and immunoblotting. The correlations of JKAP with clinical activity and inflammatory cytokines were performed. JKAP expression before and after IFX treatment was also measured. CD4+ T cells were isolated from peripheral blood in active IBD patient and HCs, and transduced with lentivirus-encoding JKAP (LV-JKAP), anti-JKAP (LV-anti-JKAP), or empty vector (LV-scramble), and JKAP functions on IBD CD4+ T cells were subsequently investigated. JKAP expression was decreased in inflamed mucosa of active IBD patients, and was negatively correlated with disease activity (CDAI, Mayo index, CRP, and ESR), IL-17 and TNF-α levels. Anti-TNF-α treatment up-regulated JKAP expression in CD patients and baseline JKAP expression was elevated in response patients compared with failure patients. Transduction of LV-JKAP into CD4+ T cells inhibited the percentages of CD25+ and CD69+ cells, and proliferation. Moreover, inhibition of JKAP promotes Th1/Th17 cell differentiation. Our data indicated that decreased expression of JKAP in intestinal mucosa contributed to the pathogenesis of IBD, through facilitating CD4+ T cell activation, proliferation, and Th1/Th17 cell differentiation.